Improving Student Nationalism Spirit Through Local Wisdom Culture on the Indonesia-Malaysia Border - Ramadhan, Iwan; Imran, Imran; Ismiyani, Nining; Prancisca, Stella; Yani T, Ahmad; Hidayah, Riama Al; Ulfah, Maria; Syahrudin, Husni; Sulistyarini, Sulistyarini (STKIP Singkawang, 2023)
Education in border areas is news that cannot be doubted, namely that there are problems regarding a sense of nationalism for students who attend school, in terms of the lack of infrastructure, and the lack of attention from the government because the area is isolated from the district and provincial capitals. Therefore, this service program aims to increase a sense of nationalism through local wisdom on the Indonesia-Malaysia border. The implementation strategy is carried out with a classical approach. Among them is the provision of material that is easily understood by students. The method of implementing the program was carried out in three sessions, namely the welcome session, delivery of material by the team, and giving stimulus to students by playing games (practice) then evaluating by distributing questionnaires about the theme of knowledge of the spirit of nationalism by linking local wisdom. Then it ends with an evaluation of understanding of the material. The results of this service are to provide an increased understanding of the spirit of nationalism, folk games based on local wisdom, national obligatory songs, and questionnaires given as a measurement of students' understanding. The rich culture of local wisdom can increase the spirit of nationalism in students as reinforcement to become more familiar with the surrounding environment in the Indonesia-Malaysia border area